350+ crochet tips, techniques, and trade secrets - Eaton, Jan (St. Martin's Griffin, 2017)
A treasury of tips, techniques, and trade secrets for crocheters provides step-by-step, illustrated instructions that cover everything from choosing the right hook and yarn to setting up a dye studio and managing yard ends.